2015
DOI: 10.26417/ejser.v5i1.p255-262
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurial Learning in Higher Education: Perceptions, Realities and Collaborative Work from the Stakeholder Point of View

Abstract: In recent years, Portuguese universities have diversified their strategies for the promotion of entrepreneurial education among (under/post)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 3 publications
0
7
0
1
Order By: Relevance
“…As a result of European, Portuguese, and Spanish directives, entrepreneurial activity has increasingly proved to be one of the privileged channels for ’making the leap’ into the labor market ( European Commission, 2013 ; Marques, 2015 ; Hervas-Oliver et al, 2017 ). Several studies indicate that are the students of business and economics who are more likely to start their own company, once they have higher levels of entrepreneurial intention (e.g., Sieger et al, 2014 ).…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…As a result of European, Portuguese, and Spanish directives, entrepreneurial activity has increasingly proved to be one of the privileged channels for ’making the leap’ into the labor market ( European Commission, 2013 ; Marques, 2015 ; Hervas-Oliver et al, 2017 ). Several studies indicate that are the students of business and economics who are more likely to start their own company, once they have higher levels of entrepreneurial intention (e.g., Sieger et al, 2014 ).…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…Entrepreneurship is increasingly becoming an alternative means of entering the labor market; the result of European and Portuguese directives aimed at universities ( European Commission, 2013 ; Marques, 2015 ). On the one hand, there is consensus that the University can be seen as a means of promoting entrepreneurship among students, and for another the study area is not relevant.…”
Section: Discussionmentioning
confidence: 99%
“…As an example, Marques and Moreira (2013) found that a typical innovative entrepreneur is a man who graduated in engineering, was motivated by opportunity, greater independence and increasing income, had high social capital, and was likely to start a business in knowledgeintensive technological sectors; whilst a typical non-innovative entrepreneur is a woman who graduated in social science, law or education, was motivated by necessity, had low social capital, and was likely to start a business in health care and education sectors. Moreover, another study found that 30.5% of the participants in entrepreneurship support programs in 2007-2013 were engineering, computer-science and technology graduates, and 19% were economics and business studies graduates (Marques et al, 2015). As a consequence, those programs do not provide equal support to different target groups.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
“…complementary strategies (Kylaheiko et al, 2011). Moreover, nascent entrepreneurs may be more prone to innovation, despite high failure rates, as typically their profile is younger and more educated than the average incumbent entrepreneur (Marques et al, 2015). The education level of the entrepreneur is partly mediated by innovation variables, in accordance to the double view of education as both providing knowledge and signaling ability.…”
Section: Introductionmentioning
confidence: 99%